Problems Faced by the Victims of Sexual Assault - Barutçu, Nesrin; Yavuz, Mehmet Fatih; Çetin, Gürsel (The Bulletin of Legal Medicine, 1999)
In this study, demographic findings obtained from a randomly selected survey among 638 victims and accused who were referred to the Department of Traumatology of the Council of Forensic Medicine in Istanbul between January 1 and June 1, 1998, are presented for reflecting violence throughout the society. Males accounted for 86.2 % of the victims and 97.3 % of the accused. Comparing the age distribution of both the victims and accused, the two groups were most frequently represented in the 3 rd decade. While females were injured more frequently due to blunt trauma, males were primarily affected by penetrating injuries. Assaults and batteries were most frequently observed in spring and were rare in winter. 39.4% of the cases were injured between 18.01 and 24.00 The assaults took place in 36% of the cases at work and work-related places, in 29% in common places, in 19.7% in domestic locations and in 10.1% sites of entertainment. 34.4% of the cases were injured by their relatives and in 5.9% by their couples, whereas victim and accused didn’t know each other in 6.3% of the cases. The majority of the victims and accused were employed in agriculture, followed by people who worked in self- employment sector.Key words: Physical Violence, Victim, Accused, Demographic Findings.
Keywords: physical violence; victim; accused; demographic findings